Simultaneous bilateral fallopian tubal pregnancy of a laparoscopic definite spontaneous unilateral ovulation: a case report - Zhen-zhen Wang; Lian-wei Xu; Li Zhao; Yi-jia Chen; Hui-cong Liu; Er-kai Yu (BMC, 2022)
Abstract Background Bilateral simultaneous fallopian tubal pregnancy is one of the rarest forms of ectopic pregnancy. Due to the lack of unique features and clinical presentation to distinguish bilateral from unilateral ectopic pregnancy, challenges the diagnosis. Case report A 27-year-old Asian woman presented with pelvic pain and vaginal bleeding. Pelvic transvaginal ultrasound showed fluid in Douglas Pouch and posterior fornix puncture revealed unclotted blood. Laparoscopic examination unveiled bilateral ectopic pregnancy with two corpus luteum visible in the right ovary, suggesting a double spontaneous unilateral ovulation. Bilateral fallopian tube fenestration and embryo extraction were performed to preserve fertility. Conclusion Diagnosis of bilateral tubal pregnancy is difficult during preoperative ultrasound examination and careful examination during laparoscopic inspection of the whole pelvic cavity to avoid missed diagnosis.